Exploring the meteorological potential for planning a high performance European electricity super-grid: Optimal power capacity distribution among countries - Santos-Alamillos, Francisco Javier; Brayshaw, David; Methven, John; Thomaidis, Nikolaos; Ruiz-Arias, José Antonio; Pozo-Vázquez, David (IOP, 2017)
The concept of a European super-grid for electricity presents clear advantages for a reliable and affordable renewable power production (photovoltaics and wind). Based on the mean-variance portfolio optimization analysis, we explore optimal scenarios for the allocation of new renewable capacity at national level in order to provide to energy decision-makers guidance about which regions should be mostly targeted to either maximize total production or reduce its day-to-day variability. The results show that the existing distribution of renewable generation capacity across Europe is far from optimal: i.e. a 'better' spatial distribution of resources could have been achieved with either a ~31% increase in mean power supply (for the same level of day-to-day variability) or a ~37.5% reduction in day-to-day variability (for the same level of mean productivity). Careful planning of additional increments in renewable capacity at the European level could, however, act to significantly ameliorate this deficiency. The choice of where to deploy resources depends, however, on the objective being pursued—if the goal is to maximize average output, then new capacity is best allocated in the countries with highest resources, whereas investment in additional capacity in a north/south dipole pattern across Europe would act to most reduce daily variations and thus decrease the day-to-day volatility of renewable power supply.
Keywords: Abastecimiento de energía; European electricity super-grid; Wind power; PV; Mean-variance portfolio; Capacity allocation